Molecular glue for phycobilisome attachment to photosystem II in Synechococcus sp. PCC 7002 - Zhenggao Zheng; Xinrui Li; Peijun Wei; Xueang Zhang; Tianyi Zhang; Zhengdong Zhang; Chunxia Dong; Jindong Zhao (Proceedings of the National Academy of Sciences, 2025)
Phycobilisomes (PBS) are the major photosynthetic light-harvesting complexes in cyanobacteria and red algae. While the structures of PBS have been determined in atomic resolutions, how PBS are attached to the reaction centers of photosystems remains less clear. Here, we report that a linker protein (LcpA) is required for the attachment of PBS to photosystem II (PSII) in the cyanobacterium Synechococcus sp. PCC 7002. We also report that the PB-loop of PBS, which is located within the α-APC domain of ApcE, is required for the attachment of PBS to PSII. Deletion of either PB-loop or the gene A0913 led to a decreased rate of photoautotrophic growth under illumination of green light, which is preferentially absorbed by PBS. A double mutant lacking the PB-loop and A0913 (ΔPBL-0913) showed a complete inhibition of O 2 evolution under the 590 nm light and could not grow under green light illumination. While assembled PBS could be isolated from ΔPBL-0913, the energy transfer from its PBS to PSII was blocked as measured by fluorescence induction. Photobleaching with intact cells showed that the PBS movement speed in ΔPBL-0913 was 2.5 times as fast as that of the wild type, suggesting that association of its PBS with thylakoids was weakened significantly. The pull-down and coimmunoprecipitation results showed that the LcpA interacts with the CP47 subunit of PSII through its N-terminal region and interacts with ApcB of PBS through its C-terminal α-helix motif. Our results provide insights into the molecular mechanism of PBS–PSII association and shed light on excitation energy transfer from PBS to PSII.